Dysexecutive disorders and their diagnosis: A position paper. (December 2018) - Godefroy, Olivier; Martinaud, Olivier; Narme, Pauline; Joseph, Pierre-Alain; Mosca, Chrystèle; Lhommée, Eugénie; Meulemans, Thierry; Czernecki, Virginie; Bertola, Céline; Labauge, Pierre; Verny, Marc; Bellmann, Anne; et al.
Abstract: Although executive function disorders are among the most prevalent cognitive impairments a consensus on diagnostic criteria has yet to be reached. With a view to harmonizing these criteria, the present position paper (i) focuses on the main dysexecutive disorders, (ii) examines recent approaches in both the behavioral and cognitive domains, (iii) defines diagnostic boundaries for frontal syndrome, (iv) reports on the frequency and profile of the executive function disorders observed in the main brain diseases, and (v) proposes an operationalization of diagnostic criteria. Future work must define the executive processes involved in human adaptive behavior, characterize their impairment in brain diseases, and improve the management of these conditions (including remediation strategies and rehabilitation).